The Effect of Carbon Emission Disclosure and Corporate Social Responsibility On The Financial Performance of Manufacturing Companies In Indonesia - Dina Maria Kristari; Armanda Yusram Teruna (Asian Journal of Social and Humanities, 2022)
This Study examines the relationship between carbon emission disclosure, corporate social responsibility (CSR), and financial performance in the manufacturing industry in Indonesia. Using data from manufacturing companies in Indonesia, this study finds a positive relationship between carbon emission disclosure and financial performance, as well as between CSR and financial performance. Companies that disclose their carbon emissions and engage in CSR initiatives are perceived positively by stakeholders, which can result in increased customer loyalty, improved reputation, and cost savings. The Indonesian government's efforts to regulate carbon emission disclosure and incentivize CSR initiatives have led to an increase in sustainable practices in the manufacturing sector. This study highlights the importance of environmental responsibility and social responsibility for companies to remain competitive and sustainable in the long term.